Confidence in the criminal justice system - Indermaur, David; Roberts, Lynne; Australian Institute of Criminology (Australian Institute of Criminology, 2009)
Confidence in the criminal justice system has emerged as a critical issue at the interface of the administration of justice and political pressures in western democracies. For more than a decade, governments in the West have felt acute pressure to make the criminal justice system more relevant, more transparent and more accountable. The 'crisis of confidence', particularly in judges and sentencing, has led to a range of high profile policy announcements seeking to 'modernise' the criminal justice system. This trend was most pronounced in the United Kingdom in the period from around 1998 to 2004 under the Blair government and led to an outpouring of analyses, investigations and reforms aimed at improving confidence in the criminal justice system. This paper reviews some of these developments but also takes a closer look at the nature of public confidence in the criminal justice system in Australia. Using the results of the latest Australian Survey of Social Attitudes, aspects of public confidence are examined with a particular focus on the evaporation of confidence in the criminal justice system from police, through courts to corrections. This 'evaporation effect' has been observed in all countries where confidence in various aspects of the criminal justice system has been studied.
"November 2009"--Caption.
Title from caption.
Includes bibliographical references (page 8)
Keywords: Crime -- Australia -- Public opinion; Criminal justice, Administration of -- Australia -- Public opinion; Australian; Electronic books